Solitary fibrous tumor of the nasal cavity- a rare case report - KC, Sudeep; Paneru, Manisha (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Solitary fibrous tumor (SFT) of the nasal cavity is a rare vascular tumor arising from adult mesenchymal stem cells. It occurs most commonly in the pleura, and in the nasal cavity, it is rare. Solitary fibrous tumors (SFTs) of the nose and paranasal sinuses are extremely rare.Case presentation: This article reports a case of a 59-year-old lady presenting with complaints of progressive nasal blockage and recurrent epistaxis. Imaging showed a mass lesion in the left nasal cavity with bone-eroding properties mimicking a malignant lesion. The patient underwent surgery, during which the mass was excised. Histopathological analysis of the specimen was consistent with SFT.Conclusion: This case highlights the importance of diagnosing SFT of the nasal cavity and paranasal sinuses, as their imaging findings and management differ from those of other tumors.